Pengaruh Metode Gamification Terhadap Keterampilan Membaca Pemahaman Teks Biografi - Purwitasari, Tiara; Tressyalina, Tressyalina; Atmazaki, Atmazaki; Nursaid, Nursaid; Nofrahadi, Nofrahadi (Paedagogie, 2026)
This study aims to describe the reading comprehension skills of biography texts among tenth-grade students of SMA Negeri 1 Ampek Angkek who were taught using the gamification method and those who were taught without using the method, as well as to determine the effect of the gamification method on students’ reading comprehension skills. This research employed an experimental approach using a Quasi Experimental Design with a Nonequivalent Control Group Design. The population consisted of 352 tenth-grade students of SMA Negeri 1 Ampek Angkek in the 2025/2026 academic year. The samples were selected through purposive sampling, namely class X.E1 as the experimental class and class X.E3 as the control class, each consisting of 35 students. Data were collected using an objective multiple-choice test and analyzed using percentage formulas, mean scores, prerequisite tests, a t-test, and N-gain calculations. The results show that students taught using the gamification method achieved higher reading comprehension skills than those taught through conventional learning. The independent sample t-test result indicates that tcount (2.87) > ttable (2.00) at a significance level of 0.05